(untitled) (Bangladesh Journal of Pharmacology, 2018)
Mastoparan B (MP-B), a cationic tetradecapeptide isolated from the venom of the Vespa basalis, exhibits cardiovascular effects, local edema and antibacterial activity. In this study, the anti-adipogenic effect of an MP-B analogue and its mechanism of action in 3T3-L1 preadipocytes were studied. The MP-B analogue (MP-B12) inhibited preadipocyte differentiation and decreased the expression of adipogenic transcription factors, including CCAAT/enhancer binding protein-alpha (C/EBPα), nuclear receptor peroxisome proliferator-activated receptor gamma (PPARγ) and sterol regulatory element-binding protein-1 (SREBP-1). Moreover, MP-B12 regulated the phosphorylation of Akt and glycogen synthase kinase-3 beta (GSK-3β), both of which play a role in preadipocyte differentiation, in which insulin and certain growth factors stimulated adipogenesis. This study demonstrates that MP-B12 inhibits preadipocyte differentiation and the accumulation of lipid droplets in 3T3-L1 preadipocytes and could potentially be used to treat obesity. Video Clip of Methodology: 4 min 11 sec Click to watch